Escaping Oil's Stranglehold: When Do States Invest in Energy Security?. (September 2015) - Cheon, Andrew; Urpelainen, Johannes
Modern economies and militaries are fundamentally dependent on oil, but the study of energy security has fallen out of favor in the field of international relations. We develop and test a theory of when and how states invest in energy security. We argue that states implement policies to improve their energy security when they perceive a risk of a militarized dispute and international oil markets are dominated by a small number of Middle Eastern producers. Empirically, we show that industrialized countries with reasons to worry about their security have significantly increased their public investment in energy research and development in response to an increase in the Middle East's share of the world oil supply.